Dietary restriction of tyrosine and phenylalanine lowers tyrosinemia associated with nitisinone therapy of alkaptonuria - Hughes, Juliette H. (J Inherit Metab Dis, 2020)
Alkaptonuria (AKU) is caused by homogentisate 1,2‐dioxygenase deficiency that leads to homogentisic acid (HGA) accumulation, ochronosis and severe osteoarthropathy. Recently, nitisinone treatment, which blocks HGA formation, has been effective in AKU patients. However, a consequence of nitisinone is elevated tyrosine that can cause keratopathy. The effect of tyrosine and phenylalanine dietary restriction was investigated in nitisinone‐treated AKU mice, and in an observational study of dietary intervention in AKU patients. Nitisinone‐treated AKU mice were fed tyrosine/phenylalanine‐free and phenylalanine‐free diets with phenylalanine supplementation in drinking water. Tyrosine metabolites were measured pre‐nitisinone, post‐nitisinone, and after dietary restriction. Subsequently an observational study was undertaken in 10 patients attending the National Alkaptonuria Centre (NAC), with tyrosine >700 μmol/L who had been advised to restrict dietary protein intake and where necessary, to use tyrosine/phenylalanine‐free amino acid supplements. Elevated tyrosine (813 μmol/L) was significantly reduced in nitisinone‐treated AKU mice fed a tyrosine/phenylalanine‐free diet in a dose responsive manner. At 3 days of restriction, tyrosine was 389.3, 274.8, and 144.3 μmol/L with decreasing phenylalanine doses. In contrast, tyrosine was not effectively reduced in mice by a phenylalanine‐free diet; at 3 days tyrosine was 757.3, 530.2, and 656.2 μmol/L, with no dose response to phenylalanine supplementation. In NAC patients, tyrosine was significantly reduced (P = .002) when restricting dietary protein alone, and when combined with tyrosine/phenylalanine‐free amino acid supplementation; 4 out of 10 patients achieved tyrosine <700 μmol/L. Tyrosine/phenylalanine dietary restriction significantly reduced nitisinone‐induced tyrosinemia in mice, with phenylalanine restriction alone proving ineffective. Similarly, protein restriction significantly reduced circulating tyrosine in AKU patients.